Penerapan DNA Rekombinan Dalam Terapi Gen - Ardandi, Rofi Yoga; Nurhaliza, Suci; Poty, Pitha Maykania; Sha, Nindy Putri; Rahmanisa, Soraya (CV. Jasa Sukses Abadi, 2024)
Recombinant DNA technology is the fusion of genetic material from two different sources. Recombinant DNA refers to combining genetic material from two different sources to create a new organism or to produce a specific protein. The main purpose of genetic recombination is to produce more evolved and adapted organisms, as well as develop biotechnology strategies, such as recombinant protein production. This technology is applied in clinical and medicine such as vaccines. Recombinant vaccines are made by utilizing recombinant DNA technology, which is a gene cloning technique that is modified to produce the specific protein product sought. Gene cloning is a procedure by which foreign DNA or genes are inserted into a host cell using a vector. Gene cloning involves the insertion of a gene of interest into a vector, resulting in the creation of recombinant DNA that can replicate within the host cell, an example being the SARS-CoV-2 DNA vaccine. Oncolytic virus, Gendicine, Modified Virus Ankara (MVA) are recombinant DNA technologies for cancer therapy. The advantages of this therapy are its ability to form new combinations of genetic material by insertion of molecules; DNA recombination technology allows the production of large quantities of certain protein molecules, which can be used in the manufacture of drugs; the production of therapeutic substances by strains of organisms can be achieved through the use of recombinant DNA technology; drugs that have unique properties that are difficult or impossible to obtain through traditional approaches can be made through DNA recombination; and DNA recombination plays an important role in drug manufacturing by facilitating the synthesis of therapeutic molecules important for human health. The disadvantages are that it has a negative impact on the environment, requires strict supervision to ensure safety and security, and ethical controversies. This technology has many benefits, but it is necessary to consider some of the disadvantages and adverse effects that can be caused.